PERSPEKTIF MASYARAKAT TERHADAP STRATEGI POLITIK UANG (MONEY POLITIC) DALAM BALUTAN BUDAYA OKO MAMA: STUDI KASUS PEMILIHAN LEGISLATIF DI DESA BAUMATA TIMUR TAHUN 2024 - Baumata Timur Village; Jorlins Elieser Humau (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Oko mama is a cultural symbol of the Atoin Meto community that traditionally functions as a medium of respect, a means of opening communication, and a tool for building social relationships. In the context of political contestation, Oko mama has undergone a shift in meaning when used by legislative candidates as a political communication strategy accompanied by the giving of money. This study aims to analyze the perspectives of the Baumata Timur Village community on the practice of money politics wrapped in Oko mama culture in the 2024 legislative elections. This study uses a qualitative approach with a phenomenological method. Data were collected through in-depth interviews, observation, and documentation with purposively selected informants, including traditional leaders, community leaders, voters, young people, women, and local elites. The results show that community perspectives are shaped by educational background, economic conditions, cultural understanding, the influence of local elites, and previous political experiences. The findings confirm that money politics in Baumata Timur Village not only occurs as an electoral violation but also operates within a cultural space that provides social legitimacy.